Influence of minerals on the thermal processing of bamboo with a suite of carbonaceous materials. (15th September 2016) - Yan, Jiefeng; Shi, Kaiqi; Pang, Chengheng; Lester, Edward; Wu, Tao
Highlights: Biomass was co-processed with carbonaceous materials with different mineral content. Synergy between biomass and different carbonaceous materials was evident. Minerals (Na, K and Ca) showed catalytic effect on co-pyrolysis and co-combustion. Abstract: This study focuses on the impacts of minerals naturally existed in different carbonaceous materials on the thermal processing of their blends with bamboo. Combustion characteristics, such as ignition temperature, peak temperature and burnout temperature, were studied using Thermogravimetric Analysis (TGA) to understand how thermal processing was affected by blending with different types of carbonaceous materials. Kinetic parameters, i.e., activation energy and pre-exponential factors, were determined for both combustion and pyrolysis processes. Synergy was observed in the co-pyrolysis of bamboo and carbonaceous materials. The blending of bamboo was found to have positive influence on ignition and burnout performance of all blends. It was showed that when graphite, activated carbon and coal were blended with bamboo by 50:50 wt%, ignition temperature of the blends dropped by 466, 90 and 142 °C, respectively and burnout temperature dropped by 82, 39 and 37 °C respectively. It was found that K and Na in biomass and Ca in coal acted as catalysts and enhanced the overall co-combustion process and resulted in significant synergistic effect.